2019
DOI: 10.1002/cne.24792
|View full text |Cite
|
Sign up to set email alerts
|

Expression mapping, quantification, and complex formation of GluD1 and GluD2 glutamate receptors in adult mouse brain

Abstract: In the cerebellum, GluD2 is exclusively expressed in Purkinje cells, where it regulates synapse formation and regeneration, synaptic plasticity, and motor learning. Delayed cognitive development in humans with GluD2 gene mutations suggests extracerebellar functions of GluD2. However, extracerebellar expression of GluD2 and its relationship with that of GluD1 are poorly understood. GluD2 mRNA and protein were widely detected, with relatively high levels observed in the olfactory glomerular layer, medial prefron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 68 publications
1
37
0
Order By: Relevance
“…Behavioral analyses under a pure C57BL/6N genetic background suggest that GluD1 plays critical roles in contextual fear memory, sociability, and depressive-like behavior. We originally developed the Grid1 +/flox mouse in which exon 4 of Grid1 gene was flanked by loxP sequences [70]. Grid1 flox/flox mice under a C57BL/6N genetic background allow us to delete the Grid1 gene in a brain region-specific manner using region-specific Cre mice or Creexpressing virus injections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral analyses under a pure C57BL/6N genetic background suggest that GluD1 plays critical roles in contextual fear memory, sociability, and depressive-like behavior. We originally developed the Grid1 +/flox mouse in which exon 4 of Grid1 gene was flanked by loxP sequences [70]. Grid1 flox/flox mice under a C57BL/6N genetic background allow us to delete the Grid1 gene in a brain region-specific manner using region-specific Cre mice or Creexpressing virus injections.…”
Section: Discussionmentioning
confidence: 99%
“…GluD1-KO mice were generated using the C57BL/6N ES cell line, RENKA [67] and maintained in a pure C57BL/6N background [70]. Briefly, exon 4 of the Grid1 gene and a Pgk promoter-driven neomycin-resistance cassette were flanked by loxP sequences (Grid1 flox ).…”
Section: Animalsmentioning
confidence: 99%
“…They are considered as glutamate receptors solely based on their strong sequence and structure homology with AMPA, NMDA and kainate receptors ( Lomeli et al, 1993 ; Araki et al, 1993 ; Schmid and Hollmann, 2008 ; Elegheert et al, 2016 ; Burada et al, 2020a ; Burada et al, 2020b ). GluD receptors are widely expressed throughout the brain, GluD1 predominantly in the forebrain, while GluD2 is highly enriched in cerebellar Purkinje cells (PCs) ( Konno et al, 2014 ; Hepp et al, 2015 ; Nakamoto et al, 2020b ). Both GluD1 and GluD2 play a role in the formation, stabilization, function and plasticity of synapses through their interaction with members of the cerebellin (Cbln) family ( Fossati et al, 2019 ; Tao et al, 2018 ; Matsuda et al, 2010 ; Kakegawa et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…GluD1, and its family member GluD2, are categorized as ionotropic receptors, but do not exhibit the typical fast ligand‐gated ion flow (Kakegawa et al, 2011). In the cerebellar cortex, GluD2 is responsible for the development, maintenance, and regeneration of parallel fiber synapses on Purkinje cells (Berridge et al, 2018; Hirano, 2012; Ichikawa, Sakimura, & Watanabe, 2016; Kashiwabuchi et al, 1995; Nakamoto, Konno, et al, 2020; Pernice et al, 2019; Yuzaki, 2011). In line with these observations, recent studies showing that ablation of GluD1 results in changes in dendritic spine density and morphology of pyramidal neurons within the medial prefrontal cortex and CA1 region of the hippocampus, support a similar role of GluD1 in maintaining synaptic integrity in forebrain nuclei (Gupta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of GluD1 function in the CNS is hampered by the limited knowledge of its subcellular localization within the mammalian brain. Although some electron microscopic data of GluD1 localization have been reported for the mouse cerebellar cortex and hippocampal formation (Hepp et al, 2015; Konno et al, 2014; Nakamoto, Konno, et al, 2020), such information is lacking for the striatum. In a recent study, Liu et al (2020) demonstrated strong GluD1 expression within the mouse dorsal striatum and provided evidence for a GluD1‐mediated regulation of the thalamostriatal projection from the parafascicular nucleus (Pf).…”
Section: Introductionmentioning
confidence: 99%